EDUKASI PENCEGAHAN DAN PENANGANAN DIARE BAGI ANAK DI PANTI ASUHAN AL-IKHLAS AMPENAN - Ulya, Tuhfatul; Budastra, Wayan Cintya Ganes; Hasina, Raisya; Safitri, Afifa Dian (Universitas Mataram, 2025)
Diarrhea is a common illness among children and remains a leading cause of death in children under five globally, including in Indonesia. The high incidence of diarrhea in children is often due to a lack of knowledge about its prevention and treatment. This activity aimed to increase the awareness of children at Al-Ikhlas Orphanage, Ampenan regarding the recognition, prevention, management, and dangers of diarrhea through a health promotion program. The method included a pre-test, interactive health education using posters, and a post-test. A total of 39 children participated in the activity. The average pre-test score was 63.5, which decreased to 61 in the post-test. This decline may be due to unfamiliar medical terms used during the session. However, the activity succeeded in raising basic awareness among the children about maintaining hygiene to prevent diarrhea. Simple and interactive health education should be further developed to improve children's understanding in orphanage environments.